2010
DOI: 10.1097/ijg.0b013e3181ca7c90
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine Levels in Patients With Normal Tension Glaucoma

Abstract: An association of elevated Hcy levels and NTG was not found and therefore a role of Hcy as a modifiable risk factor in the pathogenesis of NTG seems unlikely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
12
1
2
Order By: Relevance
“…Romano et al [26] suggested that vitamin B 12 treatment represents a powerful strategy to accelerate not only re-epithelization, but also corneal re-innervation after mechanical injury. Contradictory results have also been reported for the association between serum vitamin B 12 and glaucoma [6,9,10,11,12]. …”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Romano et al [26] suggested that vitamin B 12 treatment represents a powerful strategy to accelerate not only re-epithelization, but also corneal re-innervation after mechanical injury. Contradictory results have also been reported for the association between serum vitamin B 12 and glaucoma [6,9,10,11,12]. …”
Section: Discussionmentioning
confidence: 76%
“…From the 181 studies, 168 were excluded. Finally, 13 studies [6,7,8,9,10,11,12,13,14,19,20,21,22] were included in this meta-analysis. The detailed characteristics of each included study are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations